Recent views on cytohistological characteristics and pathogenic mechanisms of atherosclerotic lesions types I, II and III - Vuković Irena; Lačković Vesna; Raičević Ranko; Lazić Zorica; Milosavljević Zoran; Kastratović Tatjana; Mladenović-Mihailović Aleksandra; Stanković Vesna; Lačković Milena (Vojnosanitetski Pregled)
nema